Oil frying enhances flavor and sensory quality of salted dried mackerel: a comparative study of heating methods - Li, Jing; Jiang, Caiyan; Liu, Yan; Miao, Xiaoqing; Jiang, Pengfei (Frontiers in Nutrition, 2025)
This research primarily examines the effects of three thermal processes–air frying, water steaming, and oil frying–on the volatile and non-volatile flavor compounds of salted Spanish mackerel dried meat (with a salt concentration of 6% and drying durations of 4 and 6 days). The results indicated that 45 volatile flavor compounds were discovered using GC-IMS, with the oil frying group exhibiting the highest concentration of desirable volatiles. The e-tongue findings indicated that the savory flavor was the most prominent across all sample groups. According to LC-MS measurement of free amino acid content, the concentration of fresh flavor amino acids was most pronounced in the oil frying group. The oil frying group also earned the highest overall rating in the sensory evaluation. This research provides a theoretical framework for the development of prepared meals with salted and dried Spanish mackerel.